Examining sleep behavior and its association with academic performance among college students - Soni, Pallavi; Jain, Sanjay; Dhakar, Jagmohan Singh; Chanchal, Vishakha; Babu, Santosh (International Journal Of Community Medicine And Public Health, 2026)
Background: Sleep is essential for physical and mental well-being and may influence academic performance among college students. Irregular sleep habits, inadequate sleep duration, and poor sleep quality may adversely affect concentration, memory, and learning. Methods: A descriptive-correlational study was conducted among 50 college students using a structured online Likert-scale questionnaire. Sleep patterns were assessed across sleep latency, sleep duration, and sleep efficiency. Academic performance was measured using CGPA/SGPA. Descriptive statistics, reliability analysis, correlation, multiple regression, cluster analysis, and group comparison tests were performed. Results: The mean CGPA/SGPA was 7.68±1.19. Mean scores for sleep latency, sleep duration, and sleep efficiency were 3.37±0.64, 3.80±0.47, and 3.34±0.52, respectively. The sleep scale demonstrated acceptable reliability (Cronbach’s α=0.692). Significant positive correlations were observed among sleep dimensions; however, no significant correlation was found between sleep patterns and academic performance (p>0.05). Multiple regression analysis showed that sleep variables explained only 4.4% of the variance in academic performance (R2=0.044), with the overall model not statistically significant (p=0.554). Cluster analysis identified two distinct sleep behavior groups, with no significant difference in academic performance between groups. Conclusions: College students generally demonstrated moderate-to-good sleep patterns and satisfactory academic performance. Although sleep dimensions were significantly interrelated, they were not significantly associated with academic achievement. Academic performance is likely influenced by multiple factors beyond sleep behavior alone. Larger, multicentric studies are warranted to further explore these relationships.